Cryoprotective effect of an antifreeze protein purified from Tenebrio molitor larvae on vegetables. (September 2019) - Song, Da Hye; Kim, Minjae; Jin, Eon-Seon; Sim, Dae-Won; Won, Hyung-Sik; Kim, Eun Kyung; Jang, Sejin; Choi, Yong Seok; Chung, Kang-Hyun; An, Jeung Hee
Abstract: Antifreeze proteins (AFPs) are natural cryoprotectants that reduce the freezing point of water. They bind to the surface of a growing ice crystal and restrict its growth. The objectives of this study were to identify and purify the AFP from Tenebrio molitor, and to evaluate the use of this naturally occurring AFP for treating vegetables before freezing to minimize freeze-thaw damage. The purified T. molitor AFP possessed a structure similar to that of a β-helix. An amide Ι peak was evident at 1635 cm −1 using Fourier transformation infrared spectroscopy, whilst the thermal hysteresis activity of purified T. molitor AFP was around 3.5 °C at 15 mg mL −1 . Cucumber, carrot, zucchini, and onion samples treated with AFP or the control were frozen to measure their breaking force. AFP treated vegetables displayed a higher breaking force than the controls at all temperatures assessed. No change in breaking force was observed in any AFP-treated vegetable stored for 13 days at 0 °C, assuming that the breaking force at day 0 was 100%. In particular, the texture of cucumber was most effectively maintained when treated with AFP. These results indicate the potential value of the AFP from T. molitor larva in inhibiting ice crystal formation and preserving the quality of frozen vegetables. Graphical abstract: Image 1 Highlights: ● This is the first report of cryoprotective effect of an antifreeze protein from Tenebrio molitor larvae on vegetables. ● The fourier transformation infrared spectroscopy spectrum peak of antifreeze protein was assigned to helix structures. ● Antifreeze protein retains ice recrystallization inhibition activity. ● Antifreeze protein from Tenebrio molitor larvae treatment has a cryoprotective effect on onion, cucumber, carrot, zucchini texture retention at 4, 0, −2, and −20 °C for 13 days.